Association between training load, intensity, and overuse problems during pre-season in Icelandic male handball - Rafnsson, E. T.; Myklebust, G.; Valdimarsson, Ö.; Árnason, A. (Translational Sports Medicine, 2021)
In this prospective cohort study, the aim was to examine any association between pre-season training load and overuse problems (OP) in low back, knee, and shoulder in Icelandic elite male handball players. A total of 139 players participated, answering the OSTRC overuse questionnaire weekly during a 6-week period. The training volume and intensity were registered by the coaches. The average weekly OP prevalence for shoulder was 40% (95% CI 36% to 44%), for knee 33% (95% CI 28% to 38%), and for low back 31% (95% CI 26% to 36%). Substantial overuse problems (SOP) were 14% (95% CI 11% to 17%) for shoulder, 11% (95% CI 10% to 12%) for knee, and 6% (95% CI 4% to 8%) for low back. The knee was most susceptible for OP with weekly number of training and training hours associated with OP and SOP. For individual training factors, running (OP; OR = 1.30, SOP; OR = 1.59), and shooting practice (OP; OR = 1.82, SOP; OR = 3.22) had the highest associations for knee problems. Jumping was associated with OP in low back (OR = 4.55). Handball players are most susceptible for OP in knees during their pre-season. Every week, 30% participated with (SOP), affecting their performance and participation.